Effective Strategies for Early Prevention of Substance Use Disorder Among Adolescents - Anwar, Samsul; Azman, Azlinda; Jamir Singh, Paramjit Singh (Asian Social Work Journal, 2025)
Street heroin disappeared completely from the black market in 2019 in Bandung, Indonesia. This is because many heroin abusers are switching to buprenorphine/naloxone, which is more readily available and cheaper. A decade ago, Yayasan Grapiks—a non-governmental organization that works to reduce the negative effects of heroin—reported that 61 students were actively injecting buprenorphine/naloxone. Based on the report, researchers were prompted to conduct a study to analyze the background of non-heroin-addicted adolescents who were abusing buprenorphine/naloxone in Greater Bandung. Another objective is to explore appropriate strategies for early prevention of drug abuse among adolescents. Qualitative methodology with a phenomenological approach was used. In-depth interviews were conducted from September to November 2021 with 13 male and 4 female students as informants. The findings of the study show that all the informants of the study have a history of drug abuse since primary and secondary school. Before addiction to buprenorphine/naloxone, the informants were already addicted to drugs, some were even at the stage of hardcore addiction or severe addiction. Early prevention of drug abuse among adolescents is to create a positive environment at school and at home to prevent adolescents from becoming involved in drug abuse.